1995
DOI: 10.1177/0146167295215002
|View full text |Cite
|
Sign up to set email alerts
|

Hot Temperatures, Hostile Affect, Hostile Cognition, and Arousal: Tests of a General Model of Affective Aggression

Abstract: A general model of affective aggression was used to generate predictions concerning hot temperatures. Experiment 1 examined hot temperature effects on hostile affect, hostile cognition, perceived arousal, and physiological arousal in the context of a study of video games. Experiment 2 examined hot temperature effects on hostile affect, perceived and physiological arousal, and general positive and negative affect in the context of brief aerobic exercise. Consistent results were obtained. Hot temperatures produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
317
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 414 publications
(330 citation statements)
references
References 21 publications
11
317
0
2
Order By: Relevance
“…The second measure, the State Hostility Scale [Anderson et al, 1995], was used to measure aggressive feelings. This is a 35-item scale that asks participants to respond on a 1 (strongly disagree) to 5 (strongly agree) Likert Scale about how they are feeling right now.…”
Section: Methodsmentioning
confidence: 99%
“…The second measure, the State Hostility Scale [Anderson et al, 1995], was used to measure aggressive feelings. This is a 35-item scale that asks participants to respond on a 1 (strongly disagree) to 5 (strongly agree) Likert Scale about how they are feeling right now.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were then asked to complete the State Hostility Scale (SHS; Anderson et al, 1995), and to rate their perceived competence, immersion and identification with the game character.…”
Section: Methodsmentioning
confidence: 99%
“…Even with these possibilities, however, laboratory experiments in which physical discomfort or pain was deliberately established have shown that the decidedly unpleasant physical sensations in themselves can be angering and lead to affective aggression (e.g., C. A. Anderson, Deuser, & DeNeve, 1995;K. B. Anderson, Anderson, Dill, & Deuser, 1998; see also Berkowitz, 1993aBerkowitz, , 1993bBerkowitz, , 2003, perhaps particularly in people especially disposed to negative emotionality (Verona, Patrick, & Lang, 2002).…”
Section: Must There Be An External Cause Of the Negative Event?mentioning
confidence: 99%
“…Anderson et al, 1995;Baron & Bell, 1975;Baron & Richardson, 1994;Lindsay & Anderson, 2000), even in the appraisal theory camp (Stein & Levine, 1989, 1990, have also recognized the anger-aggression-eliciting effects of aversive conditions. In summarizing one of their studies, Stein and Levine (1990) concluded that their results were in accord with Berkowitz's (1983Berkowitz's ( , 1989) thesis "that aversive events .…”
Section: Aversive States Of Affairs As Anger Determinantsmentioning
confidence: 99%